A thermal model for reptiles and pelycosaurs - Florides, Georgios A.; Wrobel, L. C.; Kalogirou, Soteris A.; Tassou, Savvas A. (My University, 1999)
This paper deals with the thermal analysis of reptiles and pelycosaurs. The energy budgets affecting the body temperature of the reptile are presented. In the analysis the behaviour of the reptile, energy gains and losses due to metabolism, evaporation, solar heat, convection, and radiation are considered. The effect of the sail of pelycosaurs is also examined. Finite difference equations are derived and a computer program is written which allows also evaluation of the effect of the reptile blood flow rate. It is shown that the sail of pelycosaurs provided an advantage to the reptile by warming it up quicker in the morning in cold environments.
Keywords: Thermal modeling; Reptiles; Pelycosaurs; Dimetrodon